2012
DOI: 10.1128/jcm.06723-11
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Abbott RealTime and Roche Cobas TaqMan Hepatitis C Virus (HCV) Assays for Quantification of HCV Genotypes

Abstract: We evaluated the Abbott RealTime (ART) and Roche Cobas TaqMan Hepatitis C virus (HCV) viral load assays for quantification of HCV genotypes in patient specimens. The ART HCV assay was a more sensitive and precise tool for accurate HCV viral load quantification across the HCV genotypes tested, especially genotype 1b. Hepatitis C virus (HCV) infection is associated with significant liver-related morbidity and mortality around the world. The World Health Organization estimates that 3% of the global population is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
4
5
1
Order By: Relevance
“…These results show that the Veris HCV Assay performance is in line with that seen for other currently marketed real-time PCR molecular assays (9)(10)(11)(12)(13)(14) and fulfills the recommendations in current clinical practice guidelines for predicting a patient achieving SVR at 12 and 24 weeks posttreatment. Results were generated across multiple sites and showed comparative overall precision and consistently low LOD despite the introduction of increased variability related to the use of multiple instruments, lots, operators, and preanalytical techniques, such as sample processing, handling, and storage prior to testing.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results show that the Veris HCV Assay performance is in line with that seen for other currently marketed real-time PCR molecular assays (9)(10)(11)(12)(13)(14) and fulfills the recommendations in current clinical practice guidelines for predicting a patient achieving SVR at 12 and 24 weeks posttreatment. Results were generated across multiple sites and showed comparative overall precision and consistently low LOD despite the introduction of increased variability related to the use of multiple instruments, lots, operators, and preanalytical techniques, such as sample processing, handling, and storage prior to testing.…”
Section: Discussionsupporting
confidence: 81%
“…The SDs and % CVs were comparable with those seen with other approved HCV assays (9)(10)(11)(12)(13)(14). In this evaluation, within-run, between-lot, and between-site variability contributed most to the total imprecision seen.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Assays can perform differently by genotype [36,42,43], while detection of HCV RNA and measurement of VL for the different genotypes is crucial to clinical management of HCV-infected patients [12][13][14]. This study showed a high efficiency and accuracy of Xpert HCV VL assay for quantitation HCV RNA of GT1, GT2, GT2, GT4, and even indeterminate genotype.…”
Section: Discussionmentioning
confidence: 93%
“…Real-time polymerase chain reaction (PCR) assays are generally preferred because of their wide range of detection and sensitivity to low quantities of viral RNA (13,14). Two commercial real-time PCR platforms are the CO-BAS AmpliPrep/COBAS TaqMan HCV assay version 1.0 (CAP/ CTM v1.0) (Roche Molecular Systems, Inc., Pleasanton, CA, USA) and the Abbott RealTime HCV assay (ART) (15)(16)(17). The recently developed ART has an improved lower limit of detection of 1.08 Log international units per milliliter (IU/mL) of HCV RNA in human serum or plasma, allowing for a more sensitive quantitation of hepatitis C virus ribonucleic acid (HCV RNA) than that achieved by CAP/CTM v1.0.…”
Section: Introductionmentioning
confidence: 99%